REFERENCE HYPERTENSION CLINIC FOR PATIENTS SENT BY PRIMARY CARE PHYSICIANS: IMPACT IN BLOOD PRESSURE CONTROL, CARDIOVASCULAR AND METABOLIC RISK. (June 2018) - Salvador, P.; Rato, I.; Gregório, T.; Pinheiro, D.; Sequeira, M.; Carneiro, A.C.; Barbedo, M.; Pereira, N.; Dias, V. Paixão
ABSTRACT: Objective: A retrospective study was designed to evaluate the evolution of all patients sent to a hypertension and metabolic risk clinic, regarding blood pressure (BP) control, metabolic and cardiovascular risk. Design and method: Out of 233 patients sent by primary care physicians in 2015–2016, 9 were excluded for missing the first appointment. Results were obtained at January 31st 2017. BP objectives for each patient were determined according to 2013 ESH/ESC Guidelines. Cardiovascular risk was assessed using the European Systematic Coronary Risk Evaluation (SCORE). Results: Most common motives for consultation were suspicion of resistant (39.7%, n = 89) and secondary hypertension (29.9%, n = 67). 13.8%(n = 31) patients lost follow-up for failing consultations and 42.9%(n = 96) were discharged to primary care. The remaining 97 patients were still being followed (mean 588 days). Secondary hypertension was diagnosed in 13.0%(n = 25), although 13.0%(n = 25) were still under study. A third (33.3%, n = 70) had BP controlled at first consultation and 56.7%(n = 119) improved control, with mean decrease of 26mmHg for systolic BP and 15mmHg for diastolic BP. The number of anti-hypertensive drugs increased during follow up (p = 0.001). Renin-angiotensin system inhibitors (76.8%) and dihydropyridines calcium-channel blockers (54.0%) were the most used drugs at admission and end of follow-up (81.7%, 60.3%, respectively). A shift from thiazides (41.1% to 29.9%) towards thiazide-like diuretics (18.3% to 24.1%) appears to exist. Regarding metabolic risk, 13.8%(n = 31) were smokers, with smoke cessation being achieved in 19.6%(n = 6). 34.8%(n = 78) were medicated with statin at admission, 17.0%(n = 38) started it during follow up. Among all patients, there was a decrease in LDL, total cholesterol and triglycerides (p < 0.001, p < 0.001, p = 0.018, respectively). Patients with low-moderate SCORE risk increased from 144 to 160 (64.3 to 71.4%). If only patients whose risk could be improved are accounted for, 54.4%(n = 49) had a score decrease and 44.4%(n = 40) maintained it. Conclusions: Our results support than an active attitude leads to improvements in hypertension and metabolic risk control, being effective and important in reducing cardiovascular risk. It is also important to notice that there is still room for improvement, particularly regarding smoking cessation and a high percentage of patient missing, with the latest probably attenuating the improvements reported.